Response to Intervention and Students Who are Deaf or Hard of Hearing. (December 2013) - Luckner, John; Pierce, Corey
<x content-type="archive" xml:space="preserve">Abstract</x> Students who are deaf or hard of hearing are increasingly being educated in regular education classrooms along with their typical hearing peers. Establishing educational environments that address their unique needs is essential for their success. Response to intervention (RtI), as it is being implemented in the United States, provides a framework for educators to use to identify students who need supplemental instruction; a problem-solving process to guide data-based decision making; and a way to monitor how successful specific interventions are working for individual students in need of assistance. When properly implemented, RtI provides a dataset that allows educators to respond to students' learning needs earlier, and to make immediate tier-model instructional changes while monitoring students' growth to ensure that students meet their goals. When students do not make sufficient progress, RtI requires a change in instruction to increase students' growth rate. Doing so helps professionals better meet the needs of all students, including those who are deaf or hard of hearing, and improve overall academic performance. The purpose of this study is to provide an overview of RtI, discuss potential benefits and challenges of using an RtI framework, and to advocate for increasing the use of this model with students who are deaf or hard of hearing.